Emerging opto-operando techniques to shed light on lithium-ion batteries - Shubham Chamola; Shahab Ahmad (Next Energy)
Lithium-ion batteries (LIBs) have transformed the adoption of portable gadgets to electric vehicles over the last few years. To further their advancements towards grid energy storage and other high power applications, safety concerns need to be addressed which require a deeper understanding of complex electrochemical processes which currently limit the full potential of LIBs. Frequently used ex-situ and in-situ characterization techniques suffer from inherent challenges that require specific sample preparation and ultra-high vacuum conditions, which introduce unwanted artifacts, compromising the reliability of results. Emerging in-situ opto-operando techniques provide deeper insight into complex electrochemical processes occurring in various battery components, which remained inaccessible using conventional operando characterization techniques. In-situ opto-operando techniques exploit basic principles of optics by coupling low-energy photons (visible to IR range) into the operational battery to visualize real-time dynamics of electrochemical processes occurring at the nanoscale. This review presents a comprehensive report on recently developed in-situ opto-operando techniques and, discusses their configuration, components, working principles and provides information on Li-ion dynamics, structural changes, electrode-electrolyte compatibility, Li-solvation, solid electrolyte interface formation, etc. The development of opto-operando techniques can potentially accelerate the development of next-generation batteries. This paradigm shift, driven by insights from opto-operando techniques, promises to revolutionize the energy storage landscape, paving the way for more efficient, safer, and high-performance batteries.